THE SYNERGISTIC EFFECTS OF LIPOPEPTIDES AND BACTERIOCINS PRODUCED BY Lactobacillus sp. OF HUMAN SAMPLES AGAINST CLINICAL PATHOGENS OF WOUND INFECTION - Z.J. Khaleel; Nadhim. H. Haydar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was performed for production, purification, characterization and evaluation the antibacterial activity of biosurfactant BS which were produced from local isolate Lactobacillus plantarum Z9 with bacteriocin and studying the synergistic effect .A total 100 different samples 85(%) isolates of Lactobacillus sp. were isolated from different sources and identified by biochemical tests then subjected to the primary and secondary screening processes to select the active isolate for bacteriocin and biosurfactant production. Among the vagina isolates screened, the results found that Lactobacillus sp. Z9 isolated from the clinical samples of Iraqi healthy women had the highest productivity of the bacteriocin and biosurfactant. Partial purification of biosurfactant that produced from L. plantarum Z9 was conducted using solvent system (chloroform: methanol, 2:1). A 1:1 ratio of n-butanol was used to extract of partially purified bacteriocin, where the bacteriocin activity up to 320 AU/ml against both Staphylococcus aureus and Pseudomonas aeruginosa respectively compared to 20 AU/ml before purification.. Antibacterial activity of Bacteriocin displayed a significant activity with inhibition zones diameter ranged from (11 to 26 mm) and (10 to 25 mm) against P. aeruginosa and S. aureus at concentration ranged from 50 to 200 mg/ml. Maximum antibacterial activity of bacteriocin against P. aeruginosa and S. aureus showed at concentration 200 mg/ml of bacteriocin. Partial purified lipopeptide of L. plantarum Z9 was examined against pathogenic bacteria using well diffusion method. The lipopeptide had inhibition zones diameter ranged from (14 to 28 mm) and (13 to 29 mm) against P. aeruginosa and S. aureus respectively at concentration ranged from 25 to 200 mg/ml. The combination of lipopeptide with bacteriocin increased the range of inhibition zones and made the pathogens sensitive.